Optimizing the location choice of reverse logistics recycling network for end-of-life photovoltaic modules based on the EPR principle - Zhang, Xinyu (International Journal of Global Economics and Management, 2024)
With the rapid development of the photovoltaic (PV) industry, the collection and recycling of end-of-life PV modules is facing a new challenge. Based on the EPR principle (Extended Producer Responsibility principle), this paper investigates the location choice of reverse logistics recycling network for end-of-life PV modules from the perspective of different stakeholders. In this study, a mixed integer programming (MILP) model is established to optimize the reverse logistics network of end-of-life PV modules with the objective of minimizing the total cost of the reverse logistics network, taking into account a four-tier recycling network system with customers going to the recycling centre, dismantling and processing centre, remanufacturing centre and waste disposal agency, and three recycling solutions are designed according to the EPR principle, and the optimal solution is found with the help of CPLEX software. Optimal solution, so as to determine the siting of facilities in the network and the distribution among each node. We take Zhejiang Province, one of the leading regions in China for promoting distributed PV applications, as the research object, and plan and design the recycling network of end-of-life PV modules in Zhejiang Province, determine the siting of the network as well as the distribution of the traffic to validate the validity of the MILP model, and provide opinions and references for the recycling problem of end-of-life modules in the future.